2012
DOI: 10.1542/peds.2012-0045
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Snoring in Preschool Children: Predictors and Behavioral and Developmental Correlates

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Loud snoring, which spikes at ∼2 to 3 years of age, has been associated with behavior problems in school-aged children in cross-sectional studies, but no longitudinal studies have quantified predictors and the behavioral impact of persistent snoring in preschool-aged children.WHAT THIS STUDY ADDS: Persistent loud snoring, which occurs in 9% of children 2 to 3 years of age, is linked with behavior problems. Higher socioeconomic status and a history of breastfeeding were associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 49 publications
2
49
2
1
Order By: Relevance
“…Polysomnography and actigraphy represent more objective forms of measuring sleep and might increase the validity of the findings. Second, the version of the BEARS questionnaire used in this study did not assess snoring, which has been shown to be associated with depression and other risk behaviors (Beebe et al, 2012). Third, a larger, more diverse sample size would help make the conclusions more applicable to a general population, especially since the sample is primarily female, white, and non-Hispanic.…”
Section: Discussionmentioning
confidence: 99%
“…Polysomnography and actigraphy represent more objective forms of measuring sleep and might increase the validity of the findings. Second, the version of the BEARS questionnaire used in this study did not assess snoring, which has been shown to be associated with depression and other risk behaviors (Beebe et al, 2012). Third, a larger, more diverse sample size would help make the conclusions more applicable to a general population, especially since the sample is primarily female, white, and non-Hispanic.…”
Section: Discussionmentioning
confidence: 99%
“…1 Both habitual snoring and obstructive sleep apnea syndrome have been linked to neurodevelopmental and behavioral difficulties. 1,12,13 Data suggest that sleep disorders, including habitual snoring and obstructive sleep apnea, are under-diagnosed.…”
Section: Supporting Evidence and Rationalementioning
confidence: 99%
“…Snoring during the preschool years has also been reported to produce unfavorable effects on behavioral [18], cognitive [19] or mental development [20]. Various recent phenomena such as increases in the number of preterm babies [21], higher obesity rates in children [22], higher numbers of children with small jaws because of not chewing enough hard food [23] and higher rates of allergies in children [24] may increase the incidence of SDB in children.…”
Section: A Nationwide Viewmentioning
confidence: 99%